A STUDY ON THE FEATURES OF MINORITY-THEMED PAINTINGS IN THE 13TH NATIONAL ART EXHIBITION OF CHINA: A STUDY ON THE FEATURES OF MINORITY-THEMED PAINTINGS IN THE 13TH NATIONAL ART EXHIBITION OF CHINA - Li Zhenchao; Tetriana Ahmed Fauzi2 (Jurnal Gendang Alam (GA), 2024)
ABSTRACT This study aims to identify the features of minority-themed paintings in the 13th National Art Exhibition of China. The judging committee selected three award-winning artworks themed on minority subject. These three artworks can show us the features of minority-themed paintings distinctly. So, the researcher set these artworks as the research objective of this study. The research problems of this study are which ethnic groups the artists choose, what expressive strategies they use, and what aesthetic features are presented in these artworks. Based on exploratory research method, the researcher adopted a series of unstructured and semi-structured observation research methods to collect data, allowing the aesthetic features of each work to be revealed. By comparative analysis, the features of minority-themed paintings in this National Art Exhibition were determined. The results of this study found that these artworks exhibit their own features in three aspects: theme, content, meaning; form and structure; artist background. Specifically, the artists prefer to portray the primitive beauty of ethnic minorities, while some artists pay attention to the impact of modernization on ethnic minorities. All the artists use a realistic form to portray ethnic minorities, but they have their own considerations in structure design. The artists all have a background as university teachers, and they have conducted research on the ethnic groups for a relatively long time, which could be the basis of their research. In addition, the artists adopted a cautious attitude about the modern elements in ethnic minorities and used a restrained expressive strategy to design their artwork’s structure. This study also found that minority groups that have gradually lost their original characteristics in the process of modernization have not been selected by artists. Keywords: Aesthetic,13th National Art Exhibition of China, Minority-Themed Paintings, Realistic Form，Primitive Features